Calcium-rich biochar from crab shell: An unexpected super adsorbent for dye removal - Dai, Lichun; Zhu, Wenkun; He, Li; Tan, Furong; Zhu, Nengmin; Zhou, Qin; He, Mingxiong; Hu, Guoquan (Bioresource technology, 2018)
•Calcium-rich biochar (CRB) was directly from crab shell without modification.•CRB showed unprecedented adsorption performance for both cationic and anionic dyes.•CRB could adsorb >10,000 mg/g malachite green.•Congo red adsorption on CRB equilibrated in 2 min with a capacity >20,000 mg/g.•CRB was a low-cost but excellent dye adsorbent, thus promising in dye removal. Adsorption is the common-used method to remove dyes from wastewater, and many efforts have been made to develop low-cost but excellent adsorbents. Here, calcium-rich biochar (CRB) as a low-cost adsorbent was directly prepared from crab shell via a simple pyrolysis process without any modification. Batch adsorption results suggested that CRB was among the dye adsorbents with highest adsorption capacities and fastest adsorption rate. Specifically, it showed high adsorption capacities of 12,502 and 20,317 mg/g for cationic malachite green and anionic Congo red, respectively. The adsorption equilibrium for Congo red onto CRB could be achieved as short as 2 min. Furthermore, the dye adsorption mechanism for CRB, as investigated by zeta potential and FTIR spectra, could be attributed to electrostatic attraction, hydrogen bonding and π-π interaction. Finally, this study suggested that, attributed to its cheap source, simple synthesis process and excellent adsorption performance, CRB was promising in dye removal.